Maturation of Rhodobacter capsulatus Multicopper Oxidase CutO Depends on the CopA Copper Efflux Pathway and Requires the cutF Product - Öztürk, Yavuz; Blaby-Haas, Crysten E.; Daum, Noel; Andrei, Andreea; Rauch, Juna; Daldal, Fevzi; Koch, Hans-Georg (Frontiers in Microbiology, 2021)
Copper (Cu) is an essential cofactor required for redox enzymes in all domains of life. Because of its toxicity, tightly controlled mechanisms ensure Cu delivery for cuproenzyme biogenesis and simultaneously protect cells against toxic Cu. Many Gram-negative bacteria contain extracytoplasmic multicopper oxidases (MCOs), which are involved in periplasmic Cu detoxification. MCOs are unique cuproenzymes because their catalytic center contains multiple Cu atoms, which are required for the oxidation of Cu1+ to the less toxic Cu2+. Hence, Cu is both substrate and essential cofactor of MCOs. Here, we investigated the maturation of R. capsulatus MCO CutO and its role in periplasmic Cu detoxification. A survey of CutO activity of R. capsulatus mutants with known defects in Cu homeostasis and in the maturation of the cuproprotein cbb3-type cytochrome oxidase (cbb3-Cox) was performed. This revealed that CutO activity is largely independent of the Cu-delivery pathway for cbb3-Cox biogenesis, except for the cupric reductase CcoG, which is required for full CutO activity. The most pronounced decrease of CutO activity was observed with strains lacking the cytoplasmic Cu chaperone CopZ, or the Cu-exporting ATPase CopA, indicating that CutO maturation is linked to the CopZ-CopA mediated Cu-detoxification pathway. Our data demonstrate that CutO is important for cellular Cu resistance under both aerobic and anaerobic growth conditions. CutO is encoded in the cutFOG operon, but only CutF, and not CutG, is essential for CutO activity. No CutO activity is detectable when cutF or its putative Cu-binding motif are mutated, suggesting that the cutF product serves as a Cu-binding component required for active CutO production. Bioinformatic analyses of CutF-like proteins support their widespread roles as putative Cu-binding proteins for several Cu-relay pathways. Our overall findings show that the cytoplasmic CopZ-CopA dependent Cu detoxification pathway contributes to providing Cu to CutO maturation, a process that strictly relies on cutF.